Apuntes político-criminales en torno a la corrupción pública como delincuencia socioeconómica organizada. El caso español - Juan Terradillos Basoco (Nuevo Foro Penal, 2019)
Politic corruption, overall the one known as “grand corruption”, shares characteristics with organized economic crime. Thus, criminal policy against corruption crime must promote, initially, changes on criminal and procedural law in order to prevent behaviours from corrupt officials and corrupting individuals. But it also must introduce wideranging policies to counteract factors that encourage crime (procorruption) which are integrated into the globalized economic system.